Determinant Employee Engagement and Career Development: Analysis of Transactional Leadership, Remuneration, and Organization Commitment - Wenny Desty Febrian; Indra Sani (International Journal of Educational and Psychological Sciences, 2023)
The purpose of the study is to provide an overview of the results of previous studies and to draw conclusions from researchers. The research method is a literature review derived from research articles related to the variable in various world magazines. The purpose of this study is to identify factors that drive employee engagement, mediating variables that may directly or indirectly affect employee engagement, and what is thought to drive employee engagement in organizations. It sees the relationship between two independent variables. Previous article related to the title. It turns out that there are some significant and non-significant variables. The novelty of this study is that a new research model framework was formed, and the results of the literature review study showed the relationship between pay and employee engagement, and the results of the study showed that companies can create employee engagement. You can use the number of days as a reference.